Comparative Transcriptome Analysis Reveals Docosahexaenoic Acid and α-linolenic Acid Mediate Adhesion and Migration of Monocytes Through Distinct Gene PathwayD. (29th May 2020) - Rodway, Lisa; Pauls, Samantha; Taylor, Carla; Aukema, Harold; Zahradka, Peter
Abstract: Objectives: One of the earliest events in atherosclerotic plaque formation is the adhesion and migration of monocytes to damaged blood vessels. The fish-oil derived omega-3 fatty acid docosahexaenoic acid (DHA) has been shown to inhibit this process. There is limited evidence suggesting α-linolenic acid (ALA) has a similar effect, however, ALA has not been directly compared to DHA. Therefore, the primary objective of this study was to compare the gene expression profiles of monocytes that have been exposed to either ALA or DHA and subsequently examine the effect of these fatty acids on monocyte adhesion in a cell culture model. Methods: Whole transcriptome analysis was performed on total mRNA isolated from a human THP-1 monocyte cell line treated with ALA, DHA or vehicle for 48 h. Candidate genes identified via fold change and Ingenuity Pathway Analysis were validated by qPCR. An adhesion assay was subsequently performed on monocytes treated with ALA or DHA to corroborate the predicted outcomes of our analysis. Results: Transcriptome analysis identified a series of genes associated with cell adhesion and migration. The change in mRNA levels for each of the candidate genes was validated by qPCR, and in all cases a similar expression pattern was obtained as observed with the gene expression analysis. Based on these data, it was predicted that these processes would be upregulated in response to ALA but not DHA. The functional assay revealed that ALA increased or had no effect on monocyte adhesion, while DHA was found to significantly decrease adhesion. Conclusions: The results suggest ALA and DHA influence adhesion and migration through distinct gene pathways. Furthermore, the functional assays indicated that DHA treatment but not ALA reduces adhesion. Due to the critical role of monocyte adhesion and migration in the pathophysiology of atherosclerosis, it may be concluded from this study both DHA and ALA may exert protective effects in different ways as they relate to individuals at risk for cardiovascular disease. Funding Sources: Natural Sciences and Engineering Research Council of Canada; Canadian Institutes of Health Research.